Harmonization of Multiple SARS-CoV-2 Reference Materials Using the WHO IS (NIBSC 20/136): Results and Implications - Windsor, William Jonathan; Roell, Yannik; Tucker, Heidi; Cheng, Chi-An; Suliman, Sara; Peek, Laura J.; Pestano, Gary A.; Lee, William T.; Zeichhardt, Heinz; Lamb, Molly M.; Kammel, Martin; Wang, Hui; et al. (Frontiers in Microbiology, 2022)
Background: There is an urgent need for harmonization between SARS-CoV-2 serology platforms and assays prior to defining appropriate correlates of protection and as well inform the development of new rapid diagnostic tests that can be used for sero-surveillance as new variants of concern (VOC) emerge. We compared multiple SARS-CoV-2 serology reference materials to the WHO IS to determine their utility as secondary standards, using an international network of laboratories with high-throughput quantitative serology assays. This enabled the comparison of quantitative results between multiple serology platforms. Methods: Between April and December of 2020, thirteen well-characterized and validated SARS-CoV-2 serology reference materials were recruited from six different providers to qualify as secondary standards to the WHO International Standard. All samples were tested in parallel with NIBSC 20/136 and parallel line assays were used to compute the relevant potency and binding antibody units. Results: All samples saw varying levels of concordance between diagnostic methods at specific antigen-antibody combinations. Seven of the 12 candidate materials had high concordance for the Spike-IgG analyte (%CV between 5% and 44%). Conclusions: Despite some concordance between laboratories, qualification of secondary materials to a WHO IS using arbitrary IU or BAU/mL does not provide any benefit to the reference materials overall, due to the lack of consistent agreeable IU or BAU/mL conversions between labs. Secondary standards should be qualified to well-characterized reference materials, such as the WHO IS, using serology assays that are similar to the ones used for the original characterization of the WHO IS.